A study on employee's intention to stay in public companies in Kedah - Sanjeevkumar, Virmala (Zenith International Research & Academic Foundation (ZIRAF) India, 2012)
Without valuable employees, an organization cannot generate revenue and prosper. Retention is the most important target for the organization's Human Resources (HR) departments to achieve, and they need to explore and be aware of the real reasons, not simply people's perception, because sometiomes the high salary or pleasant working condition annot promise employees to stay in the organization. So there are more other factors that influence people's intention to stay in the organization. If the industry suffers less employee turnover, the intention of employees to stay in certain industry is higher than other industry, which indicates that this industry is healthier than others. The research problem carried out in this study is to observe the impact of 5 HRM practices (compensation, work life balance, organizational commitment, and career opportunities and supervisor support) and employees' intention to stay in public companies, Kedah Malaysia. This research will investigate the main factor which causes employee retention and why employees are preferred to stay in the public sector. The results indicate that the factors positively correlated with employee's intention to stay. The findings and recommendations were also addressed.